Nostalgia Vindicated: Psychological, Emotional, Social, Biological, and Even Political. - MILLER, Lantz Fleming (Annals of Philosophy, Social & Human Disciplines, 2024)
Long viewed as something between a malady and self-indulgence, nostalgia has recently come to be more disinterestedly explored in human sciences and philosophy. The term itself dates to a 17th Century medical doctor's investigation into the quite serious debility for soldiers in battles far from home. Currently researchers have widely assumed the phenomenon to be an emotion or mediated via emotions. Another view contends nostalgia is a social or political construct, and another suggests a biological basis. At least one observer has enjoined us to clarify the term and begin a more rigorous definition and study of nostalgia. This article takes up that challenge, approaching nostalgia from the many different (and seemingly not always consistent) facets of it. A pivot in the analysis consists in exploring two theories of what nostalgia consists in, for a sharper, more workable understanding of the phenomenon. We may thence more effectively inquire into its nature, whether indeed it is largely a socially or biologically derived phenomenon and even whether has a normative side. The article concludes that biological influences that appear to have moulded nostalgia as a phenomenon point to potential answers to normative criticisms of it as harmful and removed from reality.